Hotel 4.0: technologies and its relation with the Portuguese guest - Fernandes, Ana Rita Miranda (2018)
Due to the development of technology, this dissertation aims to explore its impact in the hospitality industry, mainly, in Portugal. The most important technologies for the Portuguese were identified as well as how the latest technologies. It was also investigated if the technology implemented in the Portuguese hotels correspond to the Portuguese needs. For the sake of understanding the task at hand, on chapter 2 – literature review – studies about the industry and technology as well as its relation with customer satisfaction were analyzed. Furthermore, the Portuguese industry and the guests’ profile were also unveiled. A questionnaire distributed among the Portuguese population was integrated as part of the study in order to analyze the underlying Portuguese expectations and needs. The results indicated that, although the respondents are pleased with technology present in the Portuguese hotels, they would change some technology to obtain the best guest experience. The respondents expressed a strong desire to experience something new. However, there were services where the traditional methods were preferred, even though they were less convenient. The Portuguese is, usually, resistant to innovation. However, the constant innovation together with the changing expectations, technologies that were once innovative become common over time. Therefore, with this dissertation, hotels may obtain updated information regarding the technology the Portuguese really wants.